8 Steps for Creating an Annual Business Plan for Dental Practice Success - Debbie Castagna (Taylor & Francis Group, 2023)
ABSTRACTBackground Understanding the steps to creating an annual business plan is a cornerstone of dental practice success. This article provides dentists and managers a blueprint for annual planning.Types of Studies Reviewed This article was written to help guide dentists to take control of their overhead and have a deeper understanding of the business side of running a successful practice. Studies reviewed include information cited by the American Dental Association, American Dental Education Association, and experts in dental Practice Management.Results There is a strong correlation between business owners who are satisfied with their practices and those who are actively involved in planning for business success. Annual planning is a process of review of prior year overhead, of the development a budget for practice expenses, personal compensation, workdays, and production goals for the upcoming year. Dentists who take control of the business aspect of their practices have a greater chance of achieving their financial goals.Practical Implications Given the importance of business acumen to running a successful practice, this process guide dentists in making well-informed decisions for themselves and their staff members.